P136 Vegan orthopaedics. (8th April 2021) - Silk, Gwithyen; Vetherajan, Niraj; Blohm, Alice; Keen, Katie; Teeling, Fiona; Sullivan, Niall
Abstract: Introduction: Bristol is the vegan capital of the UK. The UK vegan index reveals that Bristol has 360, 000 Google searches each month for Vegan content. However, do we think about the possible animal source of the medications we prescribe. Although all medications in the UK need to be tested on animals prior to being licensed and therefore cannot be truly "vegan", there are alternatives available for some commonly used medications that do not contain animal products. Several world religions prohibit their followers from consuming certain foods, ranging from those not prepared in a specific manner to those derived from certain animals. Kosher and halal diet adherents share concerns with those on vegan diets. Vegan options are a solution when only non-conforming or uncertain products are available. Methods: We conducted a review of commonly used medications in Orthopaedics and reviewed their source. The BNF, local pharmacy and online Summary of Product Characteristics (SPCs) for the medications were reviewed. Results: Where possible we have compiled a list of those that contain animal derived components and suggest alternatives. Sometimes, pharmaceutical companies cannot guarantee or differentiate the specific sources of animal-derived ingredients, as various suppliers are used in the manufacturing process and the sources can change. All unfractionated or standard heparin is porcine in origin; Rivaroxaban and Fondaparinux are simple alternatives for example. Cholecalciferol (vitamin D3) – Manufacture also involves the use of lanolin from sheep's wool. Vitamin D2 (ergocalciferol) is vegan. Conclusion: Disclosure of animal content and excipients would help patients make an informed choice. With an increasingly informed population and ethnic diversity, we should all be aware of the drugs that may contain animal products so that we can offer alternatives. Patients are more likely to adhere to prescribed medicines if they have been actively involved in prescribing decisions.